Presenting a Framework of Drivers and Strategic Factors in the Comprehensive Model of Intellectual Capital and Competitive Advantage in Startup Companies - Shafaat Tokaldan, Mahdi; Jahanshad , Azita; Pourzamani, Zahra (AI and Tech in Behavioral and Social Sciences, 2025)
The objective of the present study is to propose a framework of drivers and strategic factors within the comprehensive model of intellectual capital and competitive advantage in startup companies. This research is applied in nature and employs a descriptive-analytical approach. The methodology is qualitative. The statistical population consists of academic experts and managers of startup companies, from whom 12 individuals were selected using the snowball sampling method until reaching theoretical saturation. The data collection tool is a semi-structured interview developed based on theoretical foundations. Data analysis was conducted using thematic analysis. The findings of the qualitative phase of the research are explained in the form of two main categories and eight subcategories. The identified drivers include the following indicators: human capital, innovation capital, customer capital, and infrastructure capital. The identified strategic factors are as follows: achieving balance and optimizing the collaboration-competition mix in the industry, membership in science and technology parks and incubators, employing lean production processes, and implementing technology-based competitive strategies.